Essentials from the Golden Cabinet translation and annotation of Jin Gui Yao Lue jin gui yao lüe - Zhang, Zhongjing active 168-196 (World Scientific, 2020)
"This is a full-text English translation of Jin Gui Yao Lue, a classic book of traditional Chinese medicine. It is the oldest clinical book dedicated to internal, external, gynecological and obstetrical diseases. It is also the first medical book on differential diagnosis of diseases and symptoms, along with treatment and prescriptions. This book was originally written by Zhang Zhongjing (Zhang Ji) (150-219 CE), an eminent Chinese physician in the Eastern Han dynasty. The book consists of 25 chapters. The first chapter serves as an introduction. Chapters 2-22 discuss the diagnosis and treatment of sixty diseases, involving internal medicine, external medicine, and gynecology & obstetrics. Chapter 23 discusses emergency treatments. Chapters 24 and 25 discuss food contraindications (fowls, beasts, fruits, vegetables and grains) and treatment. The text can serve as a reference for education, research and clinical practice"--Publisher's website